Innovation portfolio management for responsible food systems transformation in the public sector: Lessons, results and recommendations from CGIAR - Schut, Marc; Colomer, Julien; Proud, Emma; Bonaiuti, Enrico; Dror, Iddo; Kang'ethe, Edwin; Esquivias, Lorena; Leeuwis, Cees (Elsevier, 2024)
CONTEXT Global food systems are confronted with multifaceted challenges, including climate change, malnutrition, and biodiversity loss, disproportionately affecting the livelihoods of millions, particularly in low- and middle-income countries. Recognizing its potential to address these challenges, innovation is increasingly central in public sector organizations. However, despite growing emphasis, the adoption of innovation portfolio management approaches remains limited.